Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan - Nurdin Nurdin; Tjipto Djuhartono (Reslaj : Religion Education Social Laa Roiba Journal, 2021)
This study aims to determine the influence of work motivation and work environment on employee performance. The research method used qualitative methods with data collection techniques through surveys. The subjects of this study were 30 employees of PT Diken Engginering in Bekasi City. Data were collected using a questionnaire instrument using a Likert scale. The validity of the data is obtained by testing the validity and reliability, all data have a normal distribution. The results showed that work motivation had a significant effect on employee performance. Likewise, the work environment has a significant influence on employee performance. The coefficient of determination (R) 2 is work motivation and the work environment has a strong relationship with employee performance by 64.7%.